Biodiversity of parasites found in the Trahira, hoplias malabaricus (Bloch, 1794), collected in the Batalha River, Tietê-Batalha Drainage Basin, SP, brazil - Gião, Thayana; Pelegrini, Larissa S. [UNESP]; DE AZEVEDO, Rodney K.; Abdallah, Vanessa Doro (My University, 2020)
Eighty-one Hoplias malabaricus specimens were collected between February 2014 and June 2016. A total of 29 species of metazoan parasites were found, 13 of which were identified as monogeneans, seven were digenean species, seven of which were nematodes, and two of which were from the subclass Hirudinea. The highest prevalence values were presented by Contracaecum sp. and Tylodelphys sp. The highest mean abundance and mean intensity was recorded by Tylodelphys sp.; the values were 36.7 ± 61.8 and 55.65 ± 69.1, respectively. The abundance of the monogenean Urocleidoides cuiabai was found to be positively correlated with host weight. The abundance of Bucephalidae gen. sp. exhibited significant positive correlations with host weight and length. For Contracaecum sp., a significant negative correlation was found between its abundance and host length and weight. No significant differences between the diversity indexes (Margalef, Pielou and Shannon) of the parasites collected in the two points were found. The Sorensen similarity index, with a value of 0.82 between the two sampling points revealed that the parasitic diversity between them is similar. The findings from this study represent new records of occurrence of H. malabaricus, as well as of Urocleidoides margolisi, Scleroductus sp. and Helobdella sp.
Keywords: Characidae; Fish parasitology; Freshwater parasites; Tietê-Batalha reservoir